Implementation of the Values of the Qur'an and Hadith in Managing Education Oriented towards the Formation of Islamic Morality - Akhyar, Muaddyl; Ilpi Zukdi; Nurfarida Deliani; Khadijah, Khadijah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze and explore the role of the Qur'an and hadith in managing education oriented towards Islamic moral development at MTsN 1 Padang Pariaman. The research method used in this research is descriptive qualitative method. This research aims to understand and describe the role of the Qur'an and hadith in managing education oriented towards Islamic moral development at MTsN 1 Padang Pariaman. The results of this study indicate that the application of the values of the Qur'an and hadith at MTsN 1 Padang Pariaman plays an important role in Islamic-based character education. By integrating religious teachings into the learning process, the school succeeds in forming students who are not only intelligent, but also have good character and noble character. The role of teachers as role models and moral coaches is crucial, as their integrity influences students in applying Islamic values. As a result, students show more disciplined, honest and tolerant behavior. This approach contributes to the birth of a younger generation who can bring Islamic values into their daily lives and become agents of positive change in society.